Smart farmers: Learning with digital technologies - Sylvester, Gerard; Davis, Kristin E.; Gammelgaard, Johanna; Preissing, John (Food and Agricultural Organization of the United Nations, 2021)
Strengthening the skills and capabilities of agricultural producers, especially smallholder producers, to successfully manage their agricultural enterprises requires sustained investment – investment that is key to transforming agri-food systems and achieving the 2030 Agenda. Digital agricultural technologies, innovations and data are transforming business models and practices across entire value chains. But can digital technologies be used to train agricultural producers or increase their skills and knowledge? This investment brief explores cases from a global study and other examples to provide insights and investment recommendations on the use of digital technologies to strengthen agriculture human capital.